2014
DOI: 10.1161/circresaha.115.303591
|View full text |Cite
|
Sign up to set email alerts
|

A Large Permissive Regulatory Domain Exclusively Controls Tbx3 Expression in the Cardiac Conduction System

Abstract: Rationale : The evolutionary conserved Tbx3 / Tbx5 gene cluster encodes T-box transcription factors that play crucial roles in the development and homeostasis of the cardiac conduction system in human and mouse. Both genes are expressed in overlapping patterns and function in strictly tissue-specific and dose-dependent manners, yet, their regulation is poorly understood. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
52
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 48 publications
4
52
0
Order By: Relevance
“…TBX3 and the adjacent gene TBX5 encode transcription factors, that have been shown to regulate the development of the cardiac conduction system. 19 Similarly, the NKX2–5 encodes a transcription factor, that is an early cue for cardiac development and has been associated with congenital heart disease 20 and heart rate 21 ( Supplementary Table 14 ). Further, reduced function of the transcription factor encoded by PITX2 has been associated with AF, shortening of the left atrial action potential, and with modulation of sodium channel blocker therapy in the adult left atrium.…”
mentioning
confidence: 99%
“…TBX3 and the adjacent gene TBX5 encode transcription factors, that have been shown to regulate the development of the cardiac conduction system. 19 Similarly, the NKX2–5 encodes a transcription factor, that is an early cue for cardiac development and has been associated with congenital heart disease 20 and heart rate 21 ( Supplementary Table 14 ). Further, reduced function of the transcription factor encoded by PITX2 has been associated with AF, shortening of the left atrial action potential, and with modulation of sodium channel blocker therapy in the adult left atrium.…”
mentioning
confidence: 99%
“…Interestingly, these data revealed that the regulatory landscape is in a preformed conformation that is similar in embryonic heart, brain and limb. Rather than the de novo formation of enhancer-promoter loops upon binding by cell-type relevant transcription factors to initiate transcription, the locus is in a fixed, permissive structure in which enhancer-promoter loops are pre-existing [40]. Such a permissive structure has previously been described for different loci, including the Hox and Shh gene loci.…”
Section: Regulation Of Tbx3 By a Large Regulatory Domainmentioning
confidence: 99%
“…Among the multiple sites contacting Tbx3 in the gene desert upstream of the gene, two evolutionary conserved enhancers have been identified that also contact each other. They are bound by cardiac-specific transcription factors Nkx2-5, Gata4, Tbx5 and Tbx3 and were shown to respond to a BMP-mediated signalling pathway to drive atrioventricular conduction system expression of Tbx3 [40].…”
Section: Regulation Of Tbx3 By a Large Regulatory Domainmentioning
confidence: 99%
See 2 more Smart Citations